THE WORLD'S EVERYDAY MESSAGE: THE INTERNATIONAL NEWS AGENCIES AND THE CHILEAN COMMUNIST PRESS DURING THE SECOND WORLD WAR - Salgado, Alfonso (Revista de Historia Social y de las Mentalidades, 2021)
This article analyses the relationship between international news agencies and the media companies of the Communist Party of Chile during World War II. Based on an analysis of Frente Popular and El Siglo and documentary evidence from a number of archives, I argue that Chilean Communists made significant efforts to provide news coming from abroad and established links with several news services, whose goals and interests differed, among which the American agencies United Press and Associated Press, the German agency Transocean, and the Soviet agency TASS played a prominent role. Nevertheless, the difficulties of obtaining a substantial amount of news from ideologically reliable sources forced them to depend in large part of US news agencies and to use these and other sources of information instrumentally.
Keywords: Communism; Press; News Agencies; Second World War